Self-care in older people with functional deficit: needs of long-term care. - Ramos, Ana (2017)
The group of 65-year-olds is becoming more numerous and with greater needs for health care. So, is necessary the reflection about new models of provision, organization, and allocation of health resources. According to the United Nations Organization, 2015, in 2050 elderly people will reach two million people (20% of the world’s population), what mean that the number of people over 60 years old will exceed a population of young people under 15 years. Parallel to aging, less healthy lifestyles have contributed to the prevalence of chronic diseases, especially cerebrovascular diseases. Hypertension and diabetes mellitus are risk factors and increase predisposition to other diseases. With aging, there is an increased risk for developing chronic, oncological and degenerative diseases, which account for more than 50% of the burden of diseases, with profound implications on independency, use of health care and services.